Critical Analysis of Sustainable Toll Road: Management of Toll Road Services and Green Facilities from The User Perspective - Amri, Lala Hucadinota Ainul; Taali, Muhammad; Farani, Dinesh Basti; Puspitasari, Dyah Ayu Kunthi; Subkhan, Muhammad Fajar (International Journal of Social and Management Studies, 2024)
Sustainable toll road development is not only related to environmentally friendly infrastructure and economic benefits but also to public acceptance of environmental issues. However, previous studies indicate that the quality of Green Toll Road services can increase the interest of toll road users through campaigns that support the environment. This study aims to analyze various aspects of sustainable toll roads in-depth, focusing on the management of environmentally friendly services and facilities. In this study, a qualitative method with a survey approach was applied by taking samples from toll road users through incidental quota sampling techniques. Service management indicators include travel satisfaction, road conditions, road infrastructure, and equipment, use of road space, and traffic management related to environmentally friendly facilities. The results obtained from toll road users indicate that ecologically friendly facilities including travel satisfaction, road conditions, road infrastructure and equipment, and traffic management have been met. However, there was a lack of standards among toll road managers, considering that toll road operators are not under the same management. The recommendation from this study is the application of consistent standards for toll road managers related to environmentally friendly aspects.